Personality styles as predictors of job satisfaction of workers in a transport company - Villegas Comesaña, Carmen Alexandra (2020)
The present study has as aim the measure of the effect of the personality over the job satisfaction. There were assessed 65 workers (74.24% male and 25.75% female) from a transportation Enterprise located in Arequipa City, with two instruments: Job Satisfaction Questionnaire by Arias and Justo (2013) and Millon’s Inventory of Personality Styles (MIPS). The results indicate low and moderate levels of job satisfaction, so as high punctuations on the personality styles such as Openness, Modification, Individualism, Sensation, Reflection, Systematization, Righteous, Conformism and Control. Moreover, there were registered differences according to the sex, marital status, educational attainment, charge, work zone. There were also several correlations between the variables, and the analysis of regression applied to measure the effects of the personality styles over the job satisfaction, were no significant.